COPD exacerbation: anthropometric characteristics of patients and the frequency of hospital admissions. - K. Y. Gashynova (Medičnì Perspektivi, 2014)
Exceptional importance of exacerbations for COPD course prognosing was reflected in the GOLD, 2011, where the number of exacerbations during the past year has been recognized as one of the main criteria of the future risks for patients. The aim of study was to determine the anthropometric indicators that increase the risk of re-hospitalization due to acute exacerbation of COPD. A retrospective analysis of medical records of inpatients who were hospitalized with COPD exacerbation to therapeutic department of CI "Dnipropetrovs’k sixth municipal clinical hospital" of Dnipropetrovsk regional council" during three years was done. It was established that neither sex, nor height, nor weight affect the rate of hospitalization due to COPD exacerbations. Older age is not a factor that increases the risk of hospitalization due to COPD exacerbation (despite the fact that the majority of hospitalized patients were elderly patients, 37% of them were persons of potentially working age). Severe exacerbation of COPD may occur in any patients with, even one year, experience of the disease. Among anthropometric indices, the most important predictor of re-hospitalization due to exacerbation of COPD is BMI<18.5, so its calculation is advisable in long-term observation of patients.